Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.5430/jnep.v4n11p82
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the academic and clinical performance of Libyan nursing students

Abstract: Background: Theoretical knowledge acquired in the classroom setting is necessary to enhance the clinical performance of nursing students in the same way that the latter reinforces what is learned in the classroom. However academic grade does not always reflect the competence of students in clinical setting. This study was conducted to determine a possible correlation between student academic performance in the nursing specialization subjects and their clinical performance. Design and Method: The research emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
3
12
0
Order By: Relevance
“…Those students who attended all the theoretical classes were about eighty-three percent [AOR = 0.83 (0.017, 0.412)] more likely to perceive themselves as competent compared to those who did not attend all the theoretical classes. This finding is supported by other studies [16,17]. This may be due to the fact that those students who attended the theoretical classes easily understand and implement their theoretical knowledge in the real clinical environment compared to those who missed the theoretical class.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Those students who attended all the theoretical classes were about eighty-three percent [AOR = 0.83 (0.017, 0.412)] more likely to perceive themselves as competent compared to those who did not attend all the theoretical classes. This finding is supported by other studies [16,17]. This may be due to the fact that those students who attended the theoretical classes easily understand and implement their theoretical knowledge in the real clinical environment compared to those who missed the theoretical class.…”
Section: Discussionsupporting
confidence: 82%
“…These included the pedagogical atmosphere of the environment, leadership style of the ward manager, premises of nursing on the ward, relationship role of the nurse teacher as enabling the integration of theory and practice, and the relationship among student, mentor, and nurse teacher [15]. Work experience, motivation, theoretical knowledge, and individual characteristic were also factors that affect the clinical competence of the students [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…This was Research apparently seen in their behaviour during clinical training, which included nursing students reporting late for work, being absent from clinical work without permission, using mobile phones during clinical working hours and lacking commitment to clinical work. A previous study [13] also reported that nursing students had a negative attitude towards clinical exposure. This was seen in their behaviour during clinical postings at hospitals, which included anxiety, feelings of vulnerability, lack of respect and loss of interest.…”
Section: Discussionmentioning
confidence: 91%
“…[6,9,14,15] Factors at an academic level that have been similarly identified are programme of study, ineffective communication, inadequate preparation and emotional reactions. [16,17] Fisher's exact test indicated no significant association between students' attitude to clinical exposure and factors influencing their attitude towards clinical exposure, although a high proportion had a positive attitude, with high reported factors affecting their attitude. This could be because of the small sample size.…”
Section: Discussionmentioning
confidence: 92%
“…Professional nurses are ideally committed to the broad aims of quality care; and their main concern to provide high standard services and to meet the needs of individual service users, their families, and communities [38 -40]. Self-efficacy influences the task employees choose to perform and the goals they set for themselves [20,21,30,31,41]. Self-efficacy can affect people's behaviour positively or negatively, and this behaviour, may have an impact on one's performance and clinical outcome for the clients [10].…”
Section: Discussionmentioning
confidence: 99%